Higher Education Crisis Communication In Indonesia In The Digital Era For Maintaining Reputation - Asfia, Nur; Sari, Eka Anisa (INJECT (Interdisciplinary Journal of Communication), 2024)
Between January and June 2024, four plagiarism issues occurred in Indonesian higher education, posing a threat to reputations that have been upheld for years. This study aims to explore the crisis communication strategies of Indonesian universities in the digital era to maintain their reputations, using a case study method and a qualitative approach. The results of the study show that there is a consistent pattern in the crisis communication employed by Indonesian higher education. According to the Situational Crisis Communication Theory, it can be concluded that the strategies employed include (1) Reminding, (2) Ingratiation and (3) Compensation, .This study found that there are both advantages and disadvantages to these strategies and offers recommendations that can be applied by other universities in Indonesia if they encounter similar issues in the future.